The effect of BCG revaccination on the response to unrelated vaccines in urban Ugandan adolescents (POPVAC C): an open-label, randomised controlled trial - Nassuuna, Jacent; Zirimenya, Ludoviko; Nkurunungi, Gyaviira; Ninsiima, Caroline; Amongi, Susan (The Lancet Global Health, 2024)
Immune responses induced by several important vaccines differ between populations, with reduced responses in low-income and rural settings compared with high-income and urban settings. BCG immunisation boosts immune responses to some unrelated vaccines in high-income populations. We aimed to test the hypothesis that BCG revaccination can enhance responses to unrelated vaccines in Ugandan schoolchildren.